2017
DOI: 10.1002/adma.201701240
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing All‐Aromatic Polyimides using Mask‐Projection Stereolithography: Processing the Nonprocessable

Abstract: High-performance, all-aromatic, insoluble, engineering thermoplastic polyimides, such as pyromellitic dianhydride and 4,4'-oxydianiline (PMDA-ODA) (Kapton), exhibit exceptional thermal stability (up to ≈600 °C) and mechanical properties (Young's modulus exceeding 2 GPa). However, their thermal resistance, which is a consequence of the all-aromatic molecular structure, prohibits processing using conventional techniques. Previous reports describe an energy-intensive sintering technique as an alternative techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 26 publications
8
122
0
1
Order By: Relevance
“…Integration of these curves yielded overall polymerization exotherm, which remained nearly constant at 12–13 W g −1 as a function of photoinitiator concentration for all samples tested (data not shown). Figure B displays time to reach heat flow maxima (s), corresponding to the maximum rate of polymerization ( R p max ), as a function of photoinitiator concentration, which reached a plateau value at the highest photoinitiator concentrations (≈1 wt%), consistent with trends described in the literature . Figure C shows shear storage modulus ( G ′) as a function of irradiation time from photorheology of the DiPhS + SH system, reaching a plateau value (GN0) more rapidly with increasing photoinitiator concentration.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Integration of these curves yielded overall polymerization exotherm, which remained nearly constant at 12–13 W g −1 as a function of photoinitiator concentration for all samples tested (data not shown). Figure B displays time to reach heat flow maxima (s), corresponding to the maximum rate of polymerization ( R p max ), as a function of photoinitiator concentration, which reached a plateau value at the highest photoinitiator concentrations (≈1 wt%), consistent with trends described in the literature . Figure C shows shear storage modulus ( G ′) as a function of irradiation time from photorheology of the DiPhS + SH system, reaching a plateau value (GN0) more rapidly with increasing photoinitiator concentration.…”
Section: Resultssupporting
confidence: 81%
“…Figure 2B , as a function of photoinitiator concentration, which reached a plateau value at the highest photoinitiator concentrations (≈1 wt%), consistent with trends described in the literature. [39] Figure 2C shows shear storage modulus (G′) as a function of irradiation time from photorheology of the DiPhS + SH system, reaching a plateau value (G N 0 ) more rapidly with increasing photoinitiator concentration. Finally, Figure 2D presents storage (G′) and loss (G″) modulus crossover, which were shown earlier to indicate gel point for stoichiometrically balanced systems far above T g , [42] as a function of photoinitiator concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Heterogeneous reactions can run more efficiently in microfluidic format due to the large surface-tovolume ratios that ensure improved phase contact and heating is much easier controllable on the microscale which significantly enhances the yield of temperature-sensitive reactions. [26,27] Additionally, it has been shown that the polymeric materials often strongly influence the success of the reaction. [21] 3D printing technologies have also been used for the fabrication of low-volume chemical batch or flow-through synthesis reactors.…”
Section: Introductionmentioning
confidence: 99%
“…[22,25] Most regular materials for SL are acrylic-or epoxy-based possessing low chemical and thermal stability, 3D-printed polytetrafluoroethylene (PTFE), and polyimides being a notable exception. [26,27] Additionally, it has been shown that the polymeric materials often strongly influence the success of the reaction. [24] Thus, there is a need for novel highly resistant materials for SL.…”
Section: Introductionmentioning
confidence: 99%